Pengaruh Iklim Mikro dan Penggunaan Media Tanam yang Berbeda pada Pertumbuan Tanaman Melon Varietas Sweet Net : The Effect of Micro Climat and Differences Planting Media on The Growth of Melon Sweet Net Varieties - Elly Daru Ika Wilujeng; Rindha Rentina Darah Pertami; Abdurrahman Salim; Majidah (Gontor Agrotech Science Journal, 2024)
Melon are plants that are sensitive to environmental changes. Currently, developing technology for cultivating melons in greenhouses is used to modify the microclimate for the growth of melon plants. This research aims to determine the effect of microclimate and different types of planting media on growth response of sweet net variety melon plants that planted in the Politeknik Negeri Jember smart green house. The research was carried out in January – May 2024. The treatments tested consisted of two treatments, namely: the use of soil media+compos and cocopeat media which would be repeated 15 times. The parameters observed include microclimate (temperature and humidity) and also plant growth indicators including plant length and number of leaves, number of flowers, and potential weight of melon. The data obtained were analyzed using the T-test. The research results show that the microclimate inside the Politeknik Negeri Jember smart green house is still classified as an optimal microclimate to support the growth of melon plants. Apart from that, the use of cocopeat planting media was able to provide the best results for the length of the melon plants in the 4th to 6th week of observation, but there was no significant difference in the parameters of the number of leaves, number of flowers and potential weight of melon of. The use of cocopeat media and soil media are both good media in supporting the growth of melon plants in a greenhouse.